Foreign Direct Investment and Macroeconomic Factors: Evidence from the Indian Economy. (March 2015) - Tripathi, Vanita; Seth, Ritika; Bhandari, Varun
Foreign direct investment (FDI) has boosted financial stability, growth and development in India. There has been positive growth rate in GDP since FDI in India has been allowed. FDI has also acted as the resistor during global financial crisis 2008. Many pull factors in India have attracted FDI which include rapidly expanding consumer market, easy access to other neighbouring countries, accessibility to cheaper basic inputs, well-developed and stable banking system and favourable policies for foreign investors, etc. This article attempts to find out the existence of relationship between FDI and six macroeconomic factors—Exchange rate (₹ per ), Inflation (WPI), GDP/IIP (proxy for Market size), Interest rate (91 days T-bills), Trade Openness and S&P CNX 500 Equity Index (profitability) using monthly and quarterly data for the period starting from July 1997 to December 2011. Apart from using the standard techniques, such as ADF and PP Unit root stationarity test, Bi-variate and Multi-variate Regression analysis and Granger Causality test, we have also applied advanced econometric techniques such as Johansen's cointegration test, Vector Auto Regression (VAR) and Impulse Response analysis to check for long-run and short-run dynamic relationship. The results show a significant correlation between FDI and all macroeconomic variables (except for Exchange rate). Causality results show that IIP/GDP, WPI and S&P CNX 500 Equity Index are Granger causing FDI inflows in India while Trade Openness is Granger caused by the same. All the macroeconomic variables taken in the article (except exchange rate) are significantly affecting FDI inflows and the overall explanatory power of the regression model (i.e., Adjusted R square) is 75.7 per cent. The results of Johansen's cointegration test disclose that there is long-run causal relation between FDI and IIP; FDI and S&P CNX 500 Equity, FDI and Trade Openness and FDI and WPI. VAR and Impulse response function analysis show that FDI is caused more by its own lagged values rather those of other macroeconomic factors. These results are important for policy makers, regulators and foreign investors. Policy makers and regulators are required to push reform agenda in domestic market for attracting huge FDI inflows in the country. Foreign investors want the policies of the country to be stable and transparent to provide enough safeguard for their investments because instability increases the risk to the foreign investors. Since, we find positive relationship between FDI and profitability, a higher investor's confidence in domestic market acts as a stimulus in getting more FDI inflows.